Chemical composition and antioxidant activity of essential oil and oleoresins of nutmeg (Myristica fragrans Houtt.) fruits - Kapoor, I. P. S. (2013)
Essential oil and oleoresins (ethanol, ethyl acetate, and iso-propyl alcohol) of Myristica fragrans were extracted by using Clevenger and Soxhlet apparatus, respectively. Gas chromatography-mass spectrometry analysis of essential oil showed the presence of 38 components representing about 99.6% of the total weight. Sabinene (29.4%) was found to be a major component along with beta pinene (10.6%), alpha pinene (10.1%), terpene-4-ol (9.6%), and several other minor components. The major component of all oleoresins contained elemicin. It has been observed that the essential oil and ethanol oleoresin showed better activity compared to other tested oleoresins and synthetic antioxidants, butylated hydroxyl anisole and butylated hydroxyl toluene. Furthermore, the activity of essential oil and oleoresins was measured for the inhibition of primary and secondary oxidation products in mustard oil by using peroxide, thiobarbituric acid, and p-anisidine values. In addition, these experiments were further supported by other complementary antioxidant assays, such as ferric thiocyanate method in a linoleic acid system, reducing power, chelating effect, and scavenging effects on 1,1′-diphenyl-2-picrylhydrazyl radical. Hence, the essential oil and ethanol oleoresin of M. fragrans could be considered as a natural food preservative.